Monte Carlo Simulation of Static and Dynamic Properties of Linear Polymer in a Crowded Environment - Deme Tesfaye Umeta; Solomon Negash Asfaw; Solomon Hailemariam Didu; Chimdessa Gashu Feyisa; Dereje Kenea Feyisa (Advances in Polymer Technology)
In this paper, we investigate the static and dynamic properties of linear polymer in the presence of obstacles. A Monte Carlo (MC) simulation method in two dimensions with a bond fluctuation model (BFM) was used to achieve this goal. To overcome the entropic barrier, we put the middle monomer of the polymer in the middle of the pore, which is placed between ordered and disordered obstacles. We probed the static properties of the polymer by calculating the mean square of the radius of gyration and the mean square end-to-end distance of the polymer, and we found that the scaling exponents of both the mean square end-to-end distance R2 and the mean square radius of gyration Rg2 as a function of the polymer length N vary with the area fraction of crowding agents, ϕ. The dynamic properties have also been studied by exploring the translocation of the polymer. Our current research shows that the escape time τ increases as ϕ increases. Moreover, in the power-law relation of escape time τ as a function of polymer length N, the scaling exponent (α) changes with ϕ. Furthermore, the study has shown that the translocation of the polymer favors the disordered barriers.